DOES FATHERS' PRENATAL MENTAL HEALTH BEAR A RELATIONSHIP TO PARENTING STRESS AT 6 MONTHS?. Issue 5 (9th August 2018) - Skjothaug, Thomas; Smith, Lars; Wentzel‐Larsen, Tore; Moe, Vibeke
ABSTRACT: This study aimed to explore fathers' mental health and retrospectively reported adverse childhood experiences during pregnancy, as well as various pathways predicting self‐reported stress at 6 months' postpartum as assessed by the Parenting Stress Index (PSI; R.R. Abidin, 1990 ). A total of 835 fathers contributed data to the study. Data collection comprised five time points during pregnancy and one at 6 months' postpartum. The main analyses were performed using linear regression and path analyses. First, linear regression analyses showed that paternal anxiety symptoms during pregnancy predicted stress scores in the PSI child domain at 6 months (coefficient = 0.36). Second, path analyses showed that depressive symptoms during pregnancy predicted parenting stress in the child domain, mediated by spousal disharmony at 6 months' postpartum (coefficient = 0.77). Third, adverse childhood experiences scores predicted parenting stress in the child domain by two different pathways: one mediated by anxiety symptoms in pregnancy (coefficient = 0.29) and the other by depressive symptoms in pregnancy and experienced spousal disharmony at 6 months' postpartum (coefficient = 0.77). The findings suggest that fathers' symptoms of anxiety and depression during pregnancy as well as adverse childhood experiences predict paternal stress and a negative perception of their children's behavior at 6 months' postpartum.